The protein levels changes due to the frying process in egg and tempeh - Mamay; Muhammad Hadi Sulhan; Andri Hartadi (Medical Laboratory Analysis and Sciences Journal, 2020)
Food is a basic need as a source of energy for humans. Food components needed by humans are consist of several constituent substances including carbohydrates, fats, vitamins, minerals, water, and protein. The most widely consumed protein sources by Indonesian people are eggs and tempeh. Processing eggs and tempeh in order to have a good taste is usually done by heating through the frying process. The frying process requires temperatures between 160-300oC. The high temperature when frying can cause protein damage so that it cannot be utilized by the human body. Therefore it is necessary to research changes in protein levels in eggs and tempeh due to heating through the frying process. The research method used was spectrophotometry with the complexing agent used was a biuret reagent. The result showed that there was decreasing content on both egg and tempeh due to the frying process. A decrease in protein content was 29.21 mg or 23.28% in eggs. Whereas in tempeh samples there was a decrease in protein content by 59.03 mg or 49.33%. Therefore the heating process in egg and tempeh should be done under 160oC